Regulation effects of rosemary (Rosmarinus officinalis Linn.) on hepatic lipid metabolism in OA induced NAFLD rats. Issue 11 (25th October 2019) - Wang, Si-Jian; Chen, Qian; Liu, Meng-Yang; Yu, Hai-Yang; Xu, Jing-Qi; Wu, Jia-Qi; Zhang, Yi; Wang, Tao
Abstract : This paper first demonstrated that rosemary has an effective function to regulate lipid metabolism through the AMPK/SREBP1c signaling pathway in vivo and in vitro . Abstract : Rosmarinus officinalis Linn. is a kind of medicinal and edible homologous plant, which is popular in the Mediterranean region with a significant effect on mind tranquilization, anti-oxidation, and metabolic improvement. However, the hypolipidemic effects and mechanism of rosemary ethanol extract (RO) and their metabolites are less known. In this study, the hypolipidemic effects of RO and its active compounds were clarified. The results showed that RO, rosmarinic acid (RA) and carnosic acid (CA) significantly reduced the contents of liver triglyceride (TG), total cholesterol (TC), free fatty acids (FFA) and improved cell hypertrophy, vacuolation, and cell necrosis in the liver of orotic acid induced non-alcoholic fatty liver disease (NAFLD) model rats. The mechanism and related pathways of RO and its main metabolites against lipid disorder were related to the up-regulation of the phosphorylation of adenosine 5′-monophosphate(AMP)-activated protein kinase (AMPK) and the inhibition of the sterol regulatory element binding protein-1c (SREBP-1c) cracking into the nucleus, following the down-regulation of fatty acid synthesis. In conclusion, our study demonstrates that RA and CA are active substances of RO, and provides scientific evidence to support functional food product development for improving NAFLD.